2021
DOI: 10.1021/jacs.0c12151
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond Photoluminescence and Photoreactivity of a Metal-Centered Excited State in a Hexacarbene–Co(III) Complex

Abstract: The photofunctionality of the cobalt−hexacarbene complex [Co(III)(PhB(MeIm) 3 ) 2 ] + (PhB(MeIm) 3 = tris(3methylimidazolin-2-ylidene)(phenyl)borate) has been investigated by time-resolved optical spectroscopy. The complex displays a weak (Φ ∼ 10 −4 ) but remarkably long-lived (τ ∼ 1 μs) orange photoluminescence at 690 nm in solution at room temperature following excitation with wavelengths shorter than 350 nm. The strongly red-shifted emission is assigned from the spectroscopic evidence and quantum chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 41 publications
2
78
0
2
Order By: Relevance
“…Chemie studies have focused on maximizing ligand field strength and on optimizing ligand bite angles,our work demonstrates that increasing the metal-ligand bond covalence through combined p-donor and p-acceptor interactions allows emission color tuning and can lead to NIR-II luminescence.Moreover, the inert and chiral nature of the [Cr(dpc) 2 ] + chromophore opens perspectives for the induction of circularly polarized emission in the NIR-II domain while using an abundant 3dmetal. These insights complement recent ground-breaking discoveries in the photophysics and the photochemistry of complexes with other first-row transition metals,i ncluding V II/III , [23,42] Mn IV , [43] Fe II , [25] Fe III , [44] Co III , [45] Ni II , [46] and Cu I . [22c, 47] It seems that much fundamental work is yet needed to fully elucidate the potential of 3d-metals for applications in luminophores,l ight harvesting, sensing,p hotocatalysis and beyond.…”
Section: Methodssupporting
confidence: 67%
“…Chemie studies have focused on maximizing ligand field strength and on optimizing ligand bite angles,our work demonstrates that increasing the metal-ligand bond covalence through combined p-donor and p-acceptor interactions allows emission color tuning and can lead to NIR-II luminescence.Moreover, the inert and chiral nature of the [Cr(dpc) 2 ] + chromophore opens perspectives for the induction of circularly polarized emission in the NIR-II domain while using an abundant 3dmetal. These insights complement recent ground-breaking discoveries in the photophysics and the photochemistry of complexes with other first-row transition metals,i ncluding V II/III , [23,42] Mn IV , [43] Fe II , [25] Fe III , [44] Co III , [45] Ni II , [46] and Cu I . [22c, 47] It seems that much fundamental work is yet needed to fully elucidate the potential of 3d-metals for applications in luminophores,l ight harvesting, sensing,p hotocatalysis and beyond.…”
Section: Methodssupporting
confidence: 67%
“…McCusker et al recently reported spectroscopical evidence of 5 MC states taking part in electron transfer reactions 25 and reactivity of MC-states is also known in chromium(III)-and cobalt(III) complexes. 26,27 The deduced relaxation cascades for Fe1 and Fe2 are compared in Fig. 4.…”
mentioning
confidence: 99%
“…This was recently accomplished for a Co III complex with the use of a scorpionate carbene ligand. 64 The same ligand has also proven useful in making an iron( iii ) (d 5 ) complex emit from a ligand-to-metal charge transfer (LMCT) excited state, applicable to photocatalytic reactions. 65,66,68 Thus, each d-electron configuration has its own photophysical characteristics, and further research in all directions seems highly desirable in the interest of broadening our understanding of photoactive excited states in first-row transition metal complexes.…”
Section: Discussionmentioning
confidence: 99%